Perkembangan Qira’at Dari Masa Klasik Ke Era Kontemporer : Kajian Terhadap Qurra’ Indonesia - Milhan (Albayan Journal of Islam and Muslim Societies, 2025)
This study investigates the historical and contemporary development of Qira'at, the variant readings of the Qur’an, tracing its origins from the Prophet Muhammad and his companions to its institutionalization and transmission by Indonesian Qurra’. The research employs a historical-analytical method by exploring classical Islamic sources and documenting the educational chains (sanad) and institutions that preserve Qira'at traditions. Findings indicate that Qira’at evolved from oral transmission among companions and tabi'in into a standardized system during the Abbasid period through the efforts of scholars like Ibn Mujahid. In the contemporary era, Qira’at has expanded globally, including in Indonesia, where it is cultivated through pesantren, madrasahs, and national institutions such as LPTQ. Indonesian Qurra’ have played a pivotal role in preserving these traditions, supported by both formal and informal educational systems. The study concludes that Qira’at remains integral to the Quranic tradition, with its continuity ensured through systematic transmission, institutional support, and increasing public interest.